P051 Lower incidence of herpes zoster in vedolizumab-treated vs. tofacitinib-treated patients with ulcerative colitis. (16th January 2018) - Caldera, F; Lasch, K; Lissoos, T; Cao, C; Bhayat, F
Abstract: Background: Patients (patients) with inflammatory bowel disease (IBD) have an increased risk of herpes zoster (HZ) compared with healthy controls. 1 Systemic immunosuppression with immunomodulators or anti-tumour necrosis factor (TNF) therapy are independent risk factors for HZ in IBD patients. 1 In patients receiving higher doses of tofacitinib (TOFA), a non-selective Janus kinase (JAK) inhibitor, HZ rates in patients with ulcerative colitis (UC), 2, rheumatoid arthritis, 3 and psoriasis 4 were higher than placebo (PBO). Vedolizumab (VDZ), a humanised monoclonal antibody with a gut-selective mechanism of action (MOA), 5, 6 may be associated with a lower risk of HZ infection compared with immunosuppressants. This retrospective post hoc analysis compared the risk of HZ infection with VDZ and TOFA in UC patients. Methods: Reported adverse events of HZ from similarly designed randomised clinical trials for VDZ (GEMINI I, N = 620 7 ) and TOFA (OCTAVE SUSTAIN, N = 394 2 in patients with UC were analysed. Patients aged ≥18 years with active UC who failed or were intolerant to ≥1 of the following were included in the studies: oral corticosteroids, azathioprine or 6-mercaptopurine, or anti-TNFα therapy. 2, 7 The number needed to harm (NNH) value was derived from the number of patients receiving either active drug or PBO who developed HZ over 52 weeks. Results: VDZ had a favourable NNH value (−2436 for the combined safety population; −257 for both ITT treatment groups combined) demonstrating that VDZ may not be associated with increased risk of HZ infection compared with PBO. TOFA showed an increased risk for HZ infection compared with PBO (NNH=36 for TOFA 5 + 10 mg [Figure 1] 8 ). VDZ dosing every 4 weeks had an NNH value of −126 while VDZ every 8 weeks had an NNH of 3843 relative to PBO. Conclusions: In these analyses, the decreased risk of HZ for VDZ relative to TOFA is possibly due to the absence of systemic immunosuppression conferred by the gut-selective MOA of VDZ. Limitations include restricted data from two different studies, small samples, the inability to access individual data, and the heterogeneity of the VDZ combined ITT and non-ITT groups. This study and medical writing assistance (Gina Moore, MS, inVentiv Medical Communications) were supported by Takeda. References: 1. Long MD, et al. (2013) Aliment Pharmacol Ther. 2. Sandborn WJ et al. (2017) New Engl J Med. 3. Winthrop KL et al. (2014) Arthritis Rheumatol. 4. Winthrop KL et al. (2017) J Am Acad Dermatol. 5. Wyant T et al. (2016) J Crohns Colitis. 6. Colombel JF et al. (2015) Gut. 7. Feagan BG et al. (2013) New Engl J Med. 8. Andrade C (2015) J Clin Psychiatry.